Residents' perceptions on the effectiveness of road humps in improving Malaysian residential environments - Bachok, Khairun Sarah Radhiah; Kadar Hamsa, Abdul Azeez; Mohamed, Mohd Zin; Ibrahim, Mansor (Avestia Publishing, 2017)
Two common concerns for residents in their respective residential areas are high traffic speeds and noise levels. This paper analyses if road humps are viable as a measure for improving residential living environment based on their effects on traffic speed and noise. The study was conducted in three Malaysian residential areas: Putrajaya, Taman Setiawangsa, and Keramat. A questionnaire survey was distributed to 478 respondents asking for their perception on whether road humps have improved the living environment by reducing speed and noise. Binary logistic regression models were also estimated using the questionnaire data regarding whether the existing road humps have improved the living environment by reducing traffic noise. Descriptive analysis was conducted to assess changes in average vehicle speeds and noise levels for the selected 12 road humps. The significance of this paper is that it explains the effect of existing Malaysian road humps on actual residential environments, which can potentially help improve the planning of new residential areas. The result of this study is that road humps are effective in reducing vehicle speeds but are not viable as a noise reduction measure. © Avestia Publishing, 2017.